Assessing fidelity of core components in a mindfulness and yoga intervention for urban youth: Applying the CORE Process. Issue 142 (June 2014) - Gould, Laura Feagans; Mendelson, Tamar; Dariotis, Jacinda K.; Ancona, Matthew; Smith, Ali S. R.; Gonzalez, Andres A.; Smith, Atman A.; Greenberg, Mark T.
Abstract : In the past years, the number of mindfulness‐based intervention and prevention programs has increased steadily. In order to achieve the intended program outcomes, program implementers need to understand the essential and indispensable components that define a program's success. This chapter describes the complex process of identifying the core components of a mindfulness and yoga program for urban early adolescents through the systematic study of fidelity of implementation of the intervention. The authors illustrate the CORE Process [(C) Conceptualize Core Components; (O) Operationalize and measure; (R) Run analyses and Review implementation findings; and (E) Enhance and refine], based on data gained from a mindfulness and yoga intervention study conducted as a community‐academic partnership in Baltimore city.